The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1088/0953-2048/20/8/014
|View full text |Cite
|
Sign up to set email alerts
|

Sample-length dependence of the critical current of slightly and significantly bent-damaged Bi2223 superconducting composite tape

Abstract: The local critical current along a sample length is different from position to position in a long sample, especially when the sample is damaged by externally applied strain. In the present work, we attempted to reveal the relation of the distribution of the local critical current to overall critical current and the sample-length dependence of critical current for slightly and significantly damaged Bi2223 composite tape samples. In the experiment, 48 cm long Bi2223 composite tape samples, composed of 48 local e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…͑2͒ below͔. 23,24,32 This function has been also used to describe the critical current distribution at weak links for analysis of V-I curve under no applied strain. 35,36 On the other hand, when the applied strain is high or the damage amount is large, it has been shown that the critical current distribution can be described by the bimodal Weibull distribution function ͓given by Eq.…”
Section: Distributions Of Measured Local and Overall Critical Cumentioning
confidence: 99%
See 4 more Smart Citations
“…͑2͒ below͔. 23,24,32 This function has been also used to describe the critical current distribution at weak links for analysis of V-I curve under no applied strain. 35,36 On the other hand, when the applied strain is high or the damage amount is large, it has been shown that the critical current distribution can be described by the bimodal Weibull distribution function ͓given by Eq.…”
Section: Distributions Of Measured Local and Overall Critical Cumentioning
confidence: 99%
“…͑3͒ later͔. 24,37 The applicability of the three parameter and bimodal functions to the present experimental results ͑Fig. 3͒ was examined as follows.…”
Section: Distributions Of Measured Local and Overall Critical Cumentioning
confidence: 99%
See 3 more Smart Citations